PENGARUH CAR, PEMBIAYAAN, NPF, DAN BOPO TERHADAP ROA BANK UMUM SYARIAH DI INDONESIA PERIODE 2010-2015 - Niode, Nenda Nurjanah; M Chabachib, M Chabachib (Faculty of Economics and Business Diponegoro University, 2016)
This study aimed to examine the effect of Capital Adequacy Ratio (CAR), Financing, Non Performing Financing (NPF), dan BOPO to profitability proxied by Return on Assets (ROA) in Islamic Banks in Indonesia 2010-2015 . The data used in this study were obtained from the Semester Financial Report for the 2010-2015 term Islamic Banks. The population in this study were 12 Islamic Banks in Indonesia. The selection of the sample using purposive sampling technique. After passing through purposive sampling stage, there are 3 samples Islamic Banks decent used namely Bank Muamalat Indonesia, Bank Syariah Mandiri, and Bank Bukopin Syariah. The analysis technique used in this study using multiple linear regression with the purpose to obtain a comprehensive picture of the relationship between variables. While the classical assumption used this research include multicolinearity, autocorrelation test, homoskedastisitas test, and test for normality. The results showed that the Capital Adequacy Ratio (CAR) have a negative and significant effect on ROA Islamic Banks. Financing variable positive and significant impact on ROA Islamic Banks. While NPF and BOPO have a negative and significant effect on ROA Islamic Banks. Predictive ability of the four variables on ROA of 96.1%, while the rest is not influenced by other factors included in the research model. The result is expected to be a guideline for the management of Islamic Banks in managing the company.